Preparing family physicians for the care of patients with severe and persistent mental illness: Examples from two U.S. residency programs. (July 2015) - Romain, Amy M; Muench, John; Phillips, Julie P
Individuals with severe and persistent mental illness have increased morbidity and mortality and significant barriers to accessing health care. Although primary care providers deliver most health care for this population, residency training programs generally lack specialized training in this area. This article describes the approaches of two family medicine residency programs in addressing this educational gap. Each program collaborated with external organizations to create service models that would enhance patient access, while immersing residents in the care of patients with severe and persistent mental illness. Residents educated in these programs gain experience with an underserved population, practice advanced skills in managing complex medical and psychiatric illness, and increase knowledge from collaborative work in unique care settings. Further implementation of programs like these, and rigorous study of such programs, could have significant benefits for family medicine education and the care of patients with severe and persistent mental illness.